You are on page 1of 2

Find the limit, if it exists :

lim (x , y ) (0,0)

x y
x 4 + y2

x
( 2 y )2 0 x 4 + y 22 x 2 y 0 x 4+ y 2 2 x 2 y

| | | |

| |

x2 y
1 x2 y
1
x3 y
1

|x| |x| 4 2 |x|


4
2
4
2
2
x +y 2 x +y
x +y 2

So :

| |

x3 y
1
|x|
4
2
2
x +y

and by taking the limits :


1
1
lim ( x , y ) (0,0) |x|= |0|=0
2
2
3
x y
lim ( x , y ) (0,0) 4 2
x +y
lim ( x , y )(0,0 ) 0

| |

we finally have :

| |
3

x y
0
4
2
x +y
0

lim ( x , y ) (0,0)

and, by the Squeeze Theorem :


x3 y
=0
x4 + y2
x3 y
=0
x 4+ y 2

lim ( x , y ) (0,0 )

| |

lim ( x , y ) (0,0)

x y 1

4
2
x +y 2

Solution by using polar coordinates. Substituting

x=cos , y=sin

we get

( cos)3 sin
=
4 cos 4 + 2 sin 2
x3 y
lim ( x , y ) (0,0 ) 4 2 =
x +y

lim ( cos , sin ) (0,0 )

2 cos 3 sin
0
lim 0 2 4
=
=0
2
4
cos +sin 0+sin
4 cos 3 sin
lim 0 4
=
cos 4 + 2 sin 2

But what if sin =0

? Well, then we also have

first expression above:


( cos)3 sin
4 cos 4 + 2 sin 2
is already zero from the beginning.

sin =0

and the